The Functional Availability of Arterial Kv7 Channels Is Suppressed Considerably by Large-Conductance Calcium-Activated Potassium Channels in 2- to 3-Month Old but Not in 10- to 15-Day Old Rats - Ma, Dongyu; Gaynullina, Dina; Schmidt, Nadine; Mladenov, Mitko; Schubert, Rudolf (Frontiers in Physiology, 2020)
Background: Voltage-gated potassium (Kv) channels, especially Kv7 channels, are major potassium channels identified in vascular smooth muscle cells with a great, albeit differential functional impact in various vessels. Vascular smooth muscle Kv7 channels always coexist with other K channels, in particular with BK channels. BK channels differ in the extent to which they influence vascular contractility. Whether this difference also causes the variability in the functional impact of Kv7 channels is unknown. Therefore, this study addressed the hypothesis that the functional impact of Kv7 channels depends on BK channels. Experimental Approach: Experiments were performed on young and adult rat Gracilis and Saphenous arteries using real-time PCR as well as pressure and wire myography. Key Results: Several subfamily members of Kv7 (Kcnq) and BK channels were expressed in A. Saphena and A. Gracilis: the highest expression was observed for BKα, BKβ1 and KCNQ4. Arterial contractility was assessed with methoxamine-induced contractions and pressure-induced myogenic responses. In vessels of adult rats, inhibition of Kv7 channels or BK channels by XE991 or IBTX, respectively enhanced arterial contractility to a similar degree, whereas activation of Kv7 channels or BK channels by retigabine or NS19504, respectively reduced arterial contractility to a similar degree. Further, IBTX increased both the contractile effect of XE991 and the anticontractile effect of retigabine, whereas NS19504 reduced the effect of retigabine and impaired the effect of XE991. In vessels of young rats, inhibition of Kv7 channels by XE991 enhanced arterial contractility much stronger than inhibition of BK channels by IBTX, whereas activation of Kv7 by retigabine reduced arterial contractility to a greater extent than activation of BK channels by NS19504. Further, IBTX increased the anticontractile effect of retigabine but not the contractile effect of XE991, whereas NS19504 reduced the effect of retigabine and impaired the effect of XE991. Conclusions: Kv7 and BK channels are expressed in young and adult rat arteries and function as negative feedback modulators in the regulation of contractility of these arteries. Importantly, BK channels govern the extent of functional impact of Kv7 channels. This effect depends on the relationship between the functional activities of BK and Kv7 channels.